Recent progress of sample stacking in capillary electrophoresis (2016-2018) - Šlampová, Andrea; Malá, Zdena; Gebauer, Petr (Electrophoresis, 2019)
Electrophoretic sample stacking comprises a group of capillary electrophoretic techniques where trace analytes from the sample are concentrated into a short zone (stack). This paper is a continuation of our previous reviews on the topic and brings a survey of more than 120 papers published approximately since the second quarter of 2016 till the first quarter of 2018. It is organized according to the particular stacking principles and includes chapters on concentration adjustment (Kohlrausch) stacking, on stacking techniques based on pH changes, on stacking in electrokinetic chromatography and on other stacking techniques. Where available, explicit information is given about the procedure, electrolyte(s) used, detector employed and sensitivity reached. Not reviewed are papers on transient isotachophoresis which are covered by another review in this issue.
Keywords: elektroforéza kapilární; látky znečišťující životní prostředí; Mice; Stacking; Environmental Pollutants; Animals; Electrophoresis; Humans; biologické markery; analýza potravin; lidé; Biomarkers; zvířata; Review; myši; Trace analysis; Food Analysis; Electrophoresis, Capillary